Crowdfunding in libraries, archives and museums. Issue 2 (8th August 2016) - Riley-Huff, Debra A.; Herrera, Kevin; Ivey, Susan; Harry, Tina
Abstract : Purpose: This paper aims to examine the fundraising strategy known as crowdfunding because it applies to galleries, libraries, archives and museums (GLAM) and to share a crowdfunding case study experience. Design/methodology/approach: A rich literature review provides the basis for understanding the central issues related to crowdfunding. Survey data provides information about the perception and experiences of other GLAM organizations with crowdfunding, and a case study shares an experience with the fundraising method. Findings: Some GLAM organizations are attempting crowdfunding projects with varied levels of success, whereas others remain unsure but curious. The case study shares one academic library's direct experience with crowdfunding. Research limitations/implications: There is little research currently available related to library use of crowdfunding. Practical implications: This paper provides a resource and research starting point for GLAM organizations interested in the crowdfunding model. Originality/value: In a comprehensive manner, this article provides much needed research on the current state of crowdfunding as it pertains to GLAM organizations.